Importance of Substrate Composition, pH and Other Variables on Tissue Factor Enhancement of Factor Vlla Activity - Neuenschwander, Pierre F; Branam, Dannielle E; Morrissey, James H (Thrombosis and Haemostasis, 1993)
Tissue factor (TF) markedly enhances the ability of factor VIIa (FVIIa) to cleave both macromolecular and small peptidyl substrates. Using soluble mutant TF (sTF) to investigate TF-enhanced FVIIa amidolytic activity in solution, we screened thirty-four commercially available peptidyl-p-nitroanilide substrates and found that substrate hydrolysis rates were influenced by both the peptide sequence and the N-terminal blocking group (MeSO2 > MeO-CO or free N-terminus >> benzoyl). Two substrates (Chromozym t-PA: MeSO2-D-Phe-Gly-Arg-pNA; and CBS 34.47: H-D-cyclohexylglycyl-α-aminobutyryl-Arg-pNA) were cleaved at rates higher than those of previously reported chromogenic substrates for FVIIa. The pH range of FVIIa amidolytic activity toward Chromozym t-PA was 6.5 to 10 with an optimum at pH 7.8, while sTF·VIIa had a higher pH optimum (pH 8.4 to 8.5). The degree of enhancement of FVIIa activity by sTF varied from 12-fold at pH 7.5 to 73-fold at pH 9.9. The effect of a variety of agents on FVIIa amidolytic activity was surveyed: most decreased activity, while glycerol and ethylene glycol enhanced the activity of FVIIa but not sTF·VIIa. These results indicate that the effect of sTF on the catalytic center of FVIIa is pH-dependent, and that certain polyalcohols can partially substitute for TF.